KUALITAS AUDIT, ENTERPRISE RISK MANAGEMENT (ERM) DAN NILAI PERUSAHAAN: PERAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) SEBAGAI MODERASI: AUDIT QUALITY, ENTERPRISE RISK MANAGEMENT (ERM) AND CORPORATE VALUE: THE ROLE OF ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) AS MODERATION - Chandra, Budi; Robby Krisyadi; Silvia Rahmadhani (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This research aims to analyze the relationship between audit quality, risk management, and environmental, social and corporate governance factors on company value and company performance. This research aims to examine the moderating influence of Environmental, Social and Governance (ESG) on the relationship between audit quality, corporate risk management (ERM), and company value and performance. In 2018–2021, fifty food and beverage companies registered on the IDX were the sample for this research. The E-views program is used in research to carry out panel data regression procedures. Firm value and performance are both positively influenced by ERM, according to the findings of this study, and there is a good relationship between ERM and ESG moderation, further supporting this conclusion. In addition, both company value and performance are positively influenced by audit quality variables, and this impact is much more pronounced when controlling for environmental, social and governance (ESG) factors. Companies, especially those in the consumer products industry, should pay attention to business value, because this is one of the metrics investors use to make investment decisions.